Proposta de um sistema de medição de desempenho que auxilie a gestão da cadeia de suprimentos: uma aplicação no setor de serviços - Santos, Tálita Floriano dos (2014)
The performance measurement is emphasized in the literature as an important feature to the supply chain management, because as it comes between a customers and suppliers relationship, it is essential a medium to evaluate if this relation is as expected. However, although to the performance measurement s significance is acknowledged and ratified, there are some difficulties on how to evaluate the performance on supply chains, especially in the service sector. Thereby, of the forms to evaluate the performance is through a performance measurement system that certifies with management models to supply chains. Accordingly, this work s goal is to propose a performance measurement system to assist in the supply chain management, with the application towards the service sector. To achieve such goal, this work adopts a quali-quantitative approach following these steps: 1) Conceptual theoretical structure s definition; 2) Choice of a focal company; 3) Mapping of current and beneath supply chains; 4) Performance indicators definition; 5) Performance metric s definition; 6) Verification of the significance of processes and metrics with AHP aid. Starting from these goals, the study proposes a performance measurement system based on the SCOR management model and it was applied in a company in the service sector and in a supplier. Starting from the conducted analysis it was found that the most important processes in decreasing order were: Source, Plan, Deliver, Make and Return. For the metrics, the most important were: perfect order fulfillment, stock cost, average answer time to a service request, deliveries carried without faults, and finally, customer complaint. Thereby, according to the seen results, it is possible to settle the most important metrics between the focal company and supplier, expecting the relationship s performance to be improved.